Deep infiltrating endometriosis: Interest of the robotic approach for a fledgling team. Issue 3 (September 2019) - Poujois, Julie; Mézan De Malartic, Cécile; Callec, Ronan; Bresler, Laurent; Hubert, Nicolas; Judlin, Philippe; Morel, Oliver
Introduction: Mini-invasive surgery of deep endometriosis is challenging. Surgical difficulties related to the technical limitations of classical laparoscopic approach might be overcome with the use of robotic assistance. The aim of this study was to evaluate the safety and feasibility of robotic surgery for deep infiltrating endometriosis in the learning phase of our team. Methods: The 20 first cases of robotic-assisted laparoscopies for endometriosis were included over a 2-year period. Baseline characteristics of patients and surgical data were reviewed. Surgical outcomes and follow-up information of the patients were analyzed. Results: Twenty women were included. The mean age was 31.9 years (range: 25–44) and mean body mass index was 23 kg/m 2 (range: 16–35). Ten patients had rectovaginal or uterosacral location only (50%) and nine women had deep infiltrating endometriosis with digestive or urinary tract lesions (45%). In addition to the gynecologic surgeon, urologic or visceral surgeons were required in 10 cases, and there were 3 cases where the three specialties were needed. The mean operative time was 183.9 min (range: 85–398) and no difference was observed between the first five cases and the last five cases. There was one laparoconversion, and only two urologic postoperative complications occurred. Conclusion: Thanks to the use of robotic surgical assistance and a multidisciplinary approach, and despite the start of the team for deep endometriosis care, no learning curve effect was observed regarding surgical procedures' success, safety, or duration. The use of robotic assistance might improve the quality of care for women facing deep endometriosis.